BETWEEN TEACHING STYLES AND ENGLISH SUBJECT: A GENDER-BASED ANALYSIS. - Eka Nur Cholifah; Eliasanti Agustina; Sukma Praiswati, Indah (Universitas Aisyah Pringsewu, 2024)
The problem of this research is to examine the differences in teaching styles of female and male lecturers. This research discusses the differences in male and female lecturers teaching styles from the perspective of EFL students in the English Language Education Department at Universitas PGRI Adi Buana Surabaya. . This study is qualitative study because this research is phenomenological-based analysis from a case in gender teaching style of lecturers.male lecturers were characterized having a firm character by EFL students during the interviews. The female instructors ask college students if the content they are given is clear and acceptable, and they do it in a flexible and friendly style. There may be differences in the pedagogy employed by male and female instructors. Studies indicate that female instructors are often more systematic thorough, and patient. In contrast, male instructors typically tie general knowledge to their lessons in an authoritative, firm, yet enjoyable manner, making learning more engaged.